2017
DOI: 10.1590/s0100-83582017350100046
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS ANALYSIS AND ANTIFUNGAL ACTIVITY OF METHANOLIC ROOT EXTRACT OF Chenopodium album AGAINST Sclerotium rolfsii

Abstract: Sclerotium rolfsii is a soil-borne fungal plant pathogen that causes diseases in more than 500 plant species. Chemical fungicides used to control this disease cause environmental pollution, therefore, plant derived compounds can be used as alternative to synthetic fungicides to reduce environmental pollution. Chenopodium album is a weed of family Chenopodiaceae that is used as food and also has medicinal importance. In the present study, antifungal activity of methanolic root extract of C. album was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 12 publications
1
22
0
2
Order By: Relevance
“…It belongs to family Chenopodiaceae. Members of this family are generally known for their antifungal activity against various fungal pathogens (Javaid and Amin, 2009;Arafat et al, 2015;Ali et al, 2017). In this study, efficacy of crude methanolic leaf extract of C. murale and its various organic fractions is reported for the management of F. oxysporum f. sp.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…It belongs to family Chenopodiaceae. Members of this family are generally known for their antifungal activity against various fungal pathogens (Javaid and Amin, 2009;Arafat et al, 2015;Ali et al, 2017). In this study, efficacy of crude methanolic leaf extract of C. murale and its various organic fractions is reported for the management of F. oxysporum f. sp.…”
Section: Introductionmentioning
confidence: 73%
“…Higher concentrations (100 and 200 mg mL -1 ) almost completely arrested the fungal growth and limited its growth up to 96%, 98% and 94% in nhexane, chloroform and ethyl acetate fractions, respectively, over control (Figure 4). Previously, members of Chenopodiaceae are known to exhibit potent antimicrobial activity against many pathogens (Singh et al, 2011;Amjad and Alizad, 2012;Ali et al, 2017). Qasem and Abu-Blan (1995) reported that extracts of C. murale possess antifungal potential against Penicillium digitatum and Alternaria solani.…”
Section: Resultsmentioning
confidence: 99%
“…However, numerous fungicides available in the market are not only toxic but also pollute the environment (Anggriani et al, 2015) and create resistance in fungal pathogens (Kim et al, 2007). A likely alternative to resolve such problems is the use of natural resources, including microorganisms and products from higher plants (De Corato et al, 2014;Ali et al, 2017;Khurshid et al, 2018). Protecting plants against fungal pathogens using such alternatives may also reduce development of resistance in the pathogens (Trigui et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…After the completion of incubation at above mentioned specified conditions, filtration of fungal biomass was done on pre-weighted filter paper and this filtered material was dried in electric oven at 70 o C to obtain a dry fungal biomass. Similar procedure was applied to all fungal species for recording biomass of selected plant pathogenic fungal species (Ali et al, 2017).…”
Section: Antifungal Assaysmentioning
confidence: 99%